PECS vs. iPad Intervention for Students with Autism Spectrum Disorders: A Literature Review - Toni Ariwijaya (The Center for Disability Studies and Services Brawijaya University, 2020)
Autism Spectrum Disorders (ASD) refers to a neurodevelopmental disorder that affects communication, behaviour and socialization of the individuals diagnosed with ASD. In children, ASD is considered as a high incidence disability since it affects one in eight children. In regard to functional communication skills of the children, effective augmentative or alternative communication process and device is highly important to facilitate positive outcomes. Both Picture Exchange Communication System (PECS) and the iPad with its communication applications are considered emerging treatment children with autism spectrum disorders (ASD). The purpose of this literature review is to compare the effectiveness of low tech intervention (through the utilization of PECS) and high tech intervention (through the utisation of iPad). The study was conducted by selecting electronic articles from several databases which were published between 2008-2018. The findings show that PECS is highly effective for increasing intentional communication skills and independence in requesting and making decisions as well as beneficial for non-English speakers. Meanwhile, iPad-based intervention is beneficial to solve children's literacy problems, to reduce stressors during interventions, and to increase the children's effective intra-verbal responses. It is then suggested that teachers, parents and care givers employ the combination of both low tech and high tech interventions as combining the two will lead to better outcomes.